Survey of ICT and Education in Africa : Malawi Country Report - Isaacs, Shafika (World Bank, Washington, DC, 2012)
This short country report, a result of larger Information for Development Program (infoDev)-supported survey of Information and Communication Technologies (ICT) in education in Africa, provides a general overview of current activities and issues related to ICT use in education in the country. A highly impoverished country, Malawi has a dedicated national ICT policy that includes the promotion of ICTs in education. It also has a few innovative initiatives in this area, committed largely to the promotion of ICT access in schools and integrated library and information services and networks.